Daughter of smoke and bone [compact disc, unabridged] - Taylor, Laini (Taylor, Laini. Daughter of smoke & bone trilogy, 2011)
Seventeen-year-old Karou, a lovely, enigmatic art student in a Prague boarding school, carries a sketchbook of hideous, frightening monsters--the chimaerae who form the only family she has ever known.